Drip irrigation of peanuts (Arachis hypogaea L. ) on a sandy soil - Feldman, S; HARTZOOK, A (Annals of Arid Zone, 2016)
The effect of two irrigation rates on the yield and quality of peanuts under drip irrigation was investigated in a sandy soil. Irrigation rates did not influence the yield, pod weight, or shelling percentage, but significantly affected the 1000 seed weight. Drip irrigation may be a positive means of saving water in the production of peanuts.